Contextualizing Qur'anic Values in Addressing Global Education Challenges: Integrating Ethics, Spirituality, and Innovation - Abid Nurhuda; Nur Muhammad Lathif; Inamul Hasan Ansori (Institut Agama Islam Sumatera Barat, 2025)
The global transformation in 21st-century education is characterized by digital disruption, epistemological competition, and a crisis of academic ethics. Amidst these conditions, the Qur'an exists not only as a religious text but also as a paradigm of values and epistemology that guides humans in the process of seeking knowledge. This article aims to reinterpret Qur'anic principles related to education, research ethics, and social responsibility by placing them in the context of global education. The approach used is a qualitative maudhu'i approach, which attempts to thematically explore Qur'anic verses related to the above themes. Then, an intertextual excavation is carried out to find interconnected meanings through literature analysis, and finally, conclusions are drawn through verification. The results of the study indicate that Qur'anic values such as scientific trustworthiness, academic honesty, openness to cross-cultural knowledge, and the integration of science and spirituality constitute a normative framework capable of guiding global education towards a just and civilized civilization. The Qur'anic-transformative education model is proposed as a solution to restore the orientation of education to a balance between technological innovation and humanitarian values.